Impact of Trade Liberalization on Economic Growth of Nepal - Khadka, Ramesh Bahadur (Janapriya Journal of Interdisciplinary Studies, 2019)
Trade openness has been considered as an important determinant of economic growth. It has been witnessed during the past couple of decades that international trade openness has played a significant role in the growth process of both developed and developing countries. International organizations such as Word Trade Organization, International Monetary Fund and World Bank are constantly advising, especially developing countries, to speed up the process of trade liberalization to achieve high economic growth. In this context, this paper aims to analyze the impact of trade liberalization on economic growth of Nepal. For this purpose, all the data regarding gross domestic product, export, import, total trade, trade balance of Nepal from 1980 A.D. to 2013 A.D. published by World Bank (2014) were used. Both descriptive as well as inferential statistics were used to analyze the data. Correlation analysis was used to find the correlation between the selected variables. Multiple linear regression analysis was carried out to analyze the impact of the trade liberalization in economic growth of Nepal. Trade cost does not explain any influence in gross domestic product, export, import, total trade and trade balance. The impact of trade openness is positive for all variables except trade balance. Trade openness has influenced economy significantly; import increased with purchasing power, export also increased but service only. Therefore, there is gap in export and imports.